Indexation and Labor market turnover in Brazil - Málaga, Guillermo (Estudios de Economía, 2016)
The issue of wage indexation in the economic literature is well understood from the point of view of its macroeconomic consequences. Nevertheless, its effects as a regulatory intervention on the labor market have been relatively less studieds. Since indexation does not correct for real effects, real shocks may create serious deviations of employed workers’ wages from current labor market conditions. This deviations may lead to an increase in labor turnover rates to adjust current costs in firms. The evidence for Brazil shows that this is, in fact, the case. Labor turnover in Brazil is extremely high compared to international rates.